2018
DOI: 10.1242/jeb.179226
|View full text |Cite
|
Sign up to set email alerts
|

Expression of calcium channel transcripts in the zebrafish heart: dominance of T-type channels

Abstract: Calcium channels are necessary for cardiac excitation-contraction (E-C) coupling, but Ca channel composition of fish hearts is still largely unknown. To this end, we determined transcript expression of Ca channels in the heart of zebrafish (), a popular model species. Altogether, 18 Ca channel α-subunit genes were expressed in both atrium and ventricle. Transcripts for 7 L-type (Ca1.1a, Ca1.1b, Ca1.2, Ca1.3a, Ca1.3b, Ca1.4a, Ca1.4b), 5 T-type (Ca3.1, Ca3.2a, Ca3.2b, Ca3.3a, Ca3.3b) and 6 P/Q-, N- and R-type (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 78 publications
(125 reference statements)
0
38
0
Order By: Relevance
“…In human ventricular cardiomyocytes, the majority of calcium responsible for muscle contraction comes from the intracellular stores of the sarcoplasmic reticulum (SR), whereas in zebrafish SR calcium release is limited, accounting for only a fraction of the calcium transient ( Bovo et al, 2013 ). In zebrafish, the main source of calcium for muscle contraction is extracellular calcium, which enters mainly via sarcolemmal T-type calcium channels ( Vornanen and Hassinen, 2016 ; Haverinen et al, 2018 ). In humans, the sarcolemmal calcium current necessary for calcium-induced calcium release occurs via L-type calcium channels, whereas significant expression of T-type calcium channels is lacking ( Gaborit et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…In human ventricular cardiomyocytes, the majority of calcium responsible for muscle contraction comes from the intracellular stores of the sarcoplasmic reticulum (SR), whereas in zebrafish SR calcium release is limited, accounting for only a fraction of the calcium transient ( Bovo et al, 2013 ). In zebrafish, the main source of calcium for muscle contraction is extracellular calcium, which enters mainly via sarcolemmal T-type calcium channels ( Vornanen and Hassinen, 2016 ; Haverinen et al, 2018 ). In humans, the sarcolemmal calcium current necessary for calcium-induced calcium release occurs via L-type calcium channels, whereas significant expression of T-type calcium channels is lacking ( Gaborit et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…The zebrafish heart is composed of an atrium and a ventricle, with many anatomical differences with the mammalian heart. However, it has been argued that the zebrafish heart physiology, heart rate (HR), and action potential, while showing some channel expression differences, are more similar to those of the human than other animal models, such as the mouse [5][6][7][8][9][10][11]. For all these reasons, the zebrafish is increasingly considered a model in cardiovascular research in phenotype-based drug and genetic screenings [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Biophysical characterization and selective drug blockade under voltage clamp conditions, allowed these authors to examine Na + , Ca 2+ , and K + in isolated zebrafish ventricular myocytes. These studies demonstrated key roles for voltage-gated Na + channels in the action potential upstroke, and L-type and T-type Ca 2+ channels in the maintenance of the plateau phase ( Nemtsas et al, 2010 ; Zhang et al, 2010 ); the prominent role of the latter being somewhat different from that in the adult mammalian ventricle ( Haverinen et al, 2018 ). Other studies suggest a prominent role for Na + -Ca 2+ exchange current at depolarized voltages during the plateau phase ( Zhang et al, 2010 ).…”
Section: Zebrafish As a Cardiac Modelmentioning
confidence: 99%